2021
DOI: 10.3390/app112411646
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Nanoscale Closed Graphene Surfaces during Fullerite C60 Hot Isostatic Pressing

Abstract: The fullerite C60 modified by hot isostatic pressing (HIP) at 0.1 GPa in argon near and beyond its thermal stability region (920–1270 K temperature interval) was studied by X-ray diffractometry, Raman spectroscopy, ultra soft X-ray photoelectron and near edge X-ray absorption fine structure spectroscopy. It was found that the C60 molecules merge into closed nanocapsules with a graphene surface during the thermal treatment. The conducted studies showed that using HIP treatment of the fullerite C60, it is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In the study, the following samples were investigated: (i) MWCNTs with average outer diameter of 80 nm and 300 µm length, synthesized in HNL of G.A. Razuvaev Institute of Organometallic Chemistry of RAS according to [17]; (ii) the 99.98% pure fullerite C 60 with a crystallite size of 0.05-0.5 mm produced by Fullerene-Center, Nizhniy Novgorod, Russia [19]; (iii) HOPG (ZYA grade) produced by SPI supplies, West Chester, PA, USA, and; (iv) the selected spongin scaffolds isolated from H. communis carbonized by the method described in [13]. The sponge was heated at 1200 • C for 1 h in an Ar stream.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, the following samples were investigated: (i) MWCNTs with average outer diameter of 80 nm and 300 µm length, synthesized in HNL of G.A. Razuvaev Institute of Organometallic Chemistry of RAS according to [17]; (ii) the 99.98% pure fullerite C 60 with a crystallite size of 0.05-0.5 mm produced by Fullerene-Center, Nizhniy Novgorod, Russia [19]; (iii) HOPG (ZYA grade) produced by SPI supplies, West Chester, PA, USA, and; (iv) the selected spongin scaffolds isolated from H. communis carbonized by the method described in [13]. The sponge was heated at 1200 • C for 1 h in an Ar stream.…”
Section: Methodsmentioning
confidence: 99%
“…The same problem arises for fullerite C 60 modified by HIP in an inert argon atmosphere. The conducted studies [17][18][19] have shown that the presence of oxygen-containing groups on the carbon material surface has a strong influence on the formation of metal-containing coating layers on the MWCNT and CSS outer surface as well as in fullerene C 60 HIP treatment. In particular, the presence of oxides on the outer surface of carbonized materials can provide good adhesion of metal coatings through the formation of carbon-oxygen-metal bridge bonds during deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 62 molecules are modeled as spherical particles. At the initial moment of time, the distance between the centers of the two nearest molecules is around 1.002 nm [38,39]. The interaction of the central molecule with smoothed C 60 is described using interatomic interaction potentials based on the Lennard-Jones potential [40,41].…”
Section: Physical Statement Of the Problemmentioning
confidence: 99%